The Impact of the Pembina Learning Model on Elementary School Students' Understanding of Cultural Diversity - Wina Dwi Puspitasari; Mubiar Agustin; Ernawulan Syaodih; Roni Rodiyana (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractMulticultural education is an important approach to making the spirit of Bhinneka Tunggal Ika the main foundation in elementary schools. By integrating the values of Bhinneka Tunggal Ika in learning, teachers can create a learning environment that respects differences, and forms citizens who are tolerant and respect diversity. The study aims to determine the impact of the Pembina learning model on elementary school students' understanding of cultural diversity. The research design uses a quasi-experimental design with a non-equivalent control group design. The experimental group used a value inquiry-based multicultural education learning model (Pembina), and the control group received ordinary learning. The research population was fourth-grade students in four elementary schools, while the control group was in three elementary schools. The results of the research show that the Pembina learning model provides an increase of 68.7% in providing an understanding of cultural diversity, and social and emotional skills of students. The findings show that this learning model contributes to forming characters who are more tolerant and respectful of cultural differences, as well as creating a deeper learning environment.Keywords: Pembina learning model, understanding of cultural diversity, multicultural education.AbstrakPendidikan multikultural merupakan pendekatan penting untuk menjadikan semangat Bhinneka Tunggal Ika sebagai landasan utama di sekolah dasar. Dengan mengintegrasikan nilai-nilai Bhinneka Tunggal Ika dalam pembelajaran, guru dapat menciptakan lingkungan belajar yang menghargai perbedaan, membentuk warga negara yang toleran dan menghargai keberagaman. Penelitian ini bertujuan untuk mengetahui dampak model pembelajaran Pembina terhadap pemahaman siswa sekolah dasar tentang keberagaman budaya. Desain penelitian menggunakan desain quasi eksperimen dengan desain kelompok kontrol non-ekuivalen. Kelompok eksperimen menggunakan model pembelajaran pendidikan multikultural berbasis inkuiri nilai (Pembina), dan kelompok kontrol menerima pembelajaran biasa. Populasi penelitian adalah siswa kelas IV di empat sekolah dasar, sedangkan kelompok kontrol di tiga sekolah dasar. Hasil penelitian menunjukkan bahwa model pembelajaran Pembina memberikan peningkatan sebesar 68,7% dalam memberikan pemahaman tentang keberagaman budaya, keterampilan sosial dan emosional siswa. Temuan penelitian menunjukkan bahwa model pembelajaran ini berkontribusi dalam membentuk karakter yang lebih toleran dan menghargai perbedaan budaya, serta menciptakan lingkungan belajar yang lebih mendalam.Kata kunci: model pembelajaran Pembina, pemahaman keberagaman budaya, pendidikan multikultural.